2022
DOI: 10.1186/s12909-022-03579-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of health sciences students’ online learning during the COVID-19 pandemic

Abstract: Background This study aims to analyse the effectiveness of distance learning during the COVID-19 pandemic among undergraduate health sciences students using systematic review. Online learning has been chosen as the best approach to continue offering education in this pandemic era. Method: The screening process was done using Scopus, ScienceDirect and PubMed based on the eligibility criteria. Out of 1486 studies, 1269 were screened. A total of 64 eligible studies obtained were included in the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 104 publications
0
22
0
Order By: Relevance
“…It should be noted that these handicaps also applied to some students in affluent countries. Nevertheless, a number of published reports indicate that most schools were able to adapt to the restrictive conditions that were forced upon their delivery of didactic material and were able to continue their educational mission successfully during the time of the pandemic 60,61 . Several papers indicate that this switch to online learning was often well‐received by teachers and learners 59,62 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that these handicaps also applied to some students in affluent countries. Nevertheless, a number of published reports indicate that most schools were able to adapt to the restrictive conditions that were forced upon their delivery of didactic material and were able to continue their educational mission successfully during the time of the pandemic 60,61 . Several papers indicate that this switch to online learning was often well‐received by teachers and learners 59,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Environmental infrastructure and properly trained instructors are necessary to ensure effective, high-quality online education ( 4 ). Opportunities such as Internet access, educational material download, and two-way communication are assumed to be provided equally so that learners can share their experiences and ideas even with time barriers ( 5 , 6 ). However, the effect of online education experienced by learners differs according to the national income level, infrastructure of the Internet, and information communication technology.…”
Section: Introductionmentioning
confidence: 99%
“…To supplement practice education, it is necessary to use a video display terminal in augmented reality technology or search for other alternatives ( 7 ). Unlike advanced countries such as the UK and US, which applied online education more than 10 years before the COVID-19 pandemic, most educational institutions and learners in developing countries such as Iran, Uganda, and Pakistan negatively evaluated online learning experiences and effects ( 5 , 8 ). However, medical students in Belgium responded that the quality of education decreased, but self-directed learning competence developed during the pandemic ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past two years of the pandemic, university learning has been largely based on the usage of distance education, later combined with face-to-face education (Naciri et al 2021 ; Dedeilia et al 2020 ; Dhawan 2020 ). Studies examining the effects of at-distance education applied to courses previously delivered in-person found that e-education did not decrease examination scores (Kronenfeld et al 2021 ) and it was also well accepted by students (Abdull Mutalib et al 2022 ; Dedeilia et al 2020 ). Costs and time-saving benefits and difficulties due to unfamiliarity with the e-education approach were reported (Monteduro, 2021 ; Sharaievska et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%